LA ARQUEOLOGÍA DESDE LA ARQUITECTURA. UNA MIRADA AL I CONGRESO INTERNACIONAL DE ARQUITECTURA ANDINA-I CIAA PERÚ 2019 - GUZMÁN JUÁREZ, Miguel (2023)
A balance of the realization of the “I International Congress of Andean Architecture-I CIAA Peru 2019” is presented, whose objective was to show and discuss the contributions of the research carried out by architects within the field of knowledge of the ancestral societies of the Andean world. However, emphasis was placed on interdisciplinary research, in such a way that these studies must be articulated with the advances of the archaeological discipline, as well as anthropological  interpretations, and these consider the former, in the sense that architecture implies reorganization of the space where the different human, daily and complex activities take place. In this logic, seven thematic symposia were proposed that allowed us to deepen certain aspects of their ways of life and their transformations. In this way, it is intended to build renewed historiographies and rethink the Andean from architecture.